The value of endocervical and endometrial lidocaine flushing before office hysteroscopy: A randomized controlled trial. Issue 1 (19th October 2019) - Shoab, Amira Y.; Maged, Ahmed M.; Ramadan, Wafaa; Dahab, Sherif; Deeb, Wesam S.; Ali, Yahia Z.A.; Mostafa, Walaa A.I.; Hussein, Eman A.
Abstract: Objective: To evaluate the safety and efficacy of flushing the cervical canal and the uterine cavity with local anesthetic in order to reduce the pain felt by patients during office hysteroscopy. Methods: A double‐blind randomized controlled trial was conducted between May 1, 2018, and February 28, 2019, involving 260 women undergoing office hysteroscopy at Kasr Al Ainy Hospital, Cairo, Egypt. Women were randomized using a computerized random number generator to intrauterine and intracervical instillation 5 minutes before the procedure of either 5 mL lidocaine 2% diluted in 15 mL normal saline, or 20 mL normal saline alone. The primary outcome measure was the visual analog scale (VAS) pain score reported by women during the procedure. Secondary outcomes included VAS score at 10 and 30 minutes after the procedure, the need for analgesia, and occurrence of vasovagal attacks. Results: Women in the lidocaine flushing group reported a significantly lower VAS score during the procedure (1.8 ± 1.1 vs 5.2 ± 1.8) and 10 and 30 minutes after it (1.3 ± 1.15 and 0.8 ± 0.9 vs 4.3 ± 2.1 and 2.98 ± 1.96) when compared with control women ( P <0.001). More women without lidocaine flushing experienced vasovagal attacks (25/130 vs 9/130, P <0.001) and needed analgesia (84/130 vs 13/130, P <0.001) when compared with women with lidocaine flushing. Conclusion: Flushing of the cervical canal and uterine cavity with local anesthetic significantly decreased pain sensation in women undergoing office hysteroscopy. ClinicalTrials.gov: NCT03530488: Abstract : Flushing of the cervical canal and uterine cavity with local anesthetic significantly decreased pain sensation in women undergoing office hysteroscopy.